POPULASI PARACOCCUS MARGINATUS WILLIAMS & GRANARA DE WILLINK PADA TANAMAN PEPAYA VARIETAS THAILAND DAN VARIETAS LOKAL DI KECAMATAN DIMEMBE KABUPATEN MINAHASA UTARA ANNA MONICA MANGARE1 - Anna Monica Mangare; Juliet M.E. Mamahit; Ventje Memah (COCOS, 2016)
ABSTRACTPapaya is a plant widely cultivated in Indonesia. One part of the plant that is oftenconsumed by people is the fruit. In Indonesia recently emerging new pest of papaya plants,the papaya mealybug Paracoccus marginatus. This study aims to determine the populationP. marginatus in thailand papaya fruit varieties and local varieties. The experiment wasconducted in three villages in the district Dimembe North Minahasa regency. Implementationof the study lasted for six months, namely from March to September 2016. This study used asurvey method in three locations that have been defined for the sampling, namely Matungkasvillage, Laikit and Dimembe. Each village selected three planting locations Thailand andlocal papaya varieties. Paerts of plants observed is the fruit. The results showed that thehighest population of mealybug P. marginatus found in papaya varieties Matungkas Thailandvillage, 49,66 grains egg, nymph 557,00 individual, 8,66 imago male individual and femaleimago 138,33 individual. Furthermore, the population in the village Laikit, namely 36,33grains egg, nymph 635,33 individual, 1,00 imago male individual and female imago 40,66individual. The next lowest is in the mralybug population Dimembe with an average of148,66 grains egg, nymph 412,00 individual, the individual 4,66 imago male and femaleimago 58,66 individually, while the local varieties found in the highest population Laikitvillage with an average of 318,66 nymph individual, and female imago 20,33 individual. Thevillage Matungkas second highest with an average of 55,00 grains egg, nymph 214,00individual, 1,00 imago male individual and female imago 40,66 individual. FurthermoreDimembe village which is the lowest population, seen from an egg stadia grains 36,00,214,33 nymph individual, and female imago 38,33 stadia individual.Keyword : Population, Papaya, Paracoccus marginatus.